Analisis Sistem Akuntansi Penggajian Karyawan Pada PT.Nuansa Dharma Cipta Di Samarinda - Daury Rahadian Sriandanda, Nia Rachmawati Eddy Soegiarto2 (EKONOMIA, 2021)
The purpose of this thesis research is to determine and analyze the implementation of the payroll accounting system of PT. Nuansa Dharma Cipta in Samarinda.Researchers conducted an analysis of the payroll system at PT. Nuansa Dharma Cipta in Samarinda by using analysis techniques, namely by comparing the payroll accounting system applied in the company with the payroll accounting system according to Mulyadi theory and using a flow chart. Attached is an interview or question and answer process in the form of a questionnaire with related sections, namely: Manager (1 person), Accounting Section (1 person), Cashier (2 people).Â The results of the analysis that have been carried out, are supported by the results of a questionnaire from 88 question items to 4 respondents with a percentage of 68% answers. This means that PT. Nuansa Dharma Cipta in Samarinda are quite appropriate to meet the payroll accounting system according to Mulyadi theory. However, there are several things that need to be considered again. Based on this, it can be seen that the hypothesis proposed by the researcher was rejected, because the payroll accounting system at PT. Nuansa Dharma Cipta in Samarinda are quite in accordance with the payroll accounting system according to Mulyadi theory.